Assessing the professionalism of nursing internship students from the perspective of educational instructors students in Namazi Hospital of Shiraz University of Medical Sciences in 2021 - Sara Shafian; Maryam Naeem-Zadeh; Mahmoud-Reza Dehghani; Batool Amiri; Azadeh Azemian (Medicina Clínica Práctica, 2024)
Background: Professionalism is a multidimensional and evolving structure with has socio-cultural information that affects patient satisfaction, and health care outcomes. An important part of nurses' professional behavior is formed during their student years and through education and learning. The aim of this study was assessing the professionalism in internship nursing student. Methods: This cross-sectional study was conducted in Shiraz University of Medical Sciences. The data collection instrument was a nursing professionalism questionnaire that was completed by 2 instructors for 70 final-year nursing students in the internship. Method of sampling used non-probability convenience sampling. The data were analyzed using SPSS, version 16, for Windows (SPSS Inc., Chicago, IL, USA). Descriptive statistics (mean and percentage) were used to describe demographic characteristics and mean scores of professionalisms and its dimensions. Histograms and the bias-kurtosis and Shapiro–Wilk test were used to evaluate the normality. Comparisons between the two groups were made by independent samples t-test. To compare more groups, the Kruskal–Walli’s test was used. Result: The findings of this study show that the mean score of professionalism was 75.26(±10.5), the highest mean was related to the dimension of behavior based on professional values and norms (80.36 ± 9.93) and the lowest mean was related to the dimension of professional interactions (75.00 ± 13.72). Students with perfect regular participation in their internship had a significantly higher professionalism score than other students (P-value = .0001). There was no significant relationship between students' gender and score professionalism (P < .571). Conclusion: Given the importance of familiarity of undergraduate students with the concepts of professionalism in theory, providing practical training of these concepts through experienced instructors and role models can be an effective step in developing professionalism in nurses after their graduation. Resumen: Antecedentes: el profesionalismo es una estructura multidimensional y en evolución con información sociocultural que afecta la satisfacción del paciente y los resultados de la atención médica. Una parte importante del comportamiento profesional de las enfermeras se forma durante sus años de estudiante y a través de la educación y el aprendizaje. El objetivo de este estudio fue evaluar el profesionalismo en estudiantes de enfermería en prácticas. Métodos: Este estudio transversal se realizó en la Universidad de Ciencias Médicas de Shiraz. El instrumento de recolección de datos fue un cuestionario de profesionalismo de enfermería que fue completado por dos instructores para 70 estudiantes del último año de enfermería en el internado. Método de muestreo utilizado Muestreo no probabilístico por conveniencia. Los datos se analizaron con SPSS, versión 16, para Windows (SPSS Inc., Chicago, IL, EE. UU.). Se utilizaron estadísticas descriptivas (media y porcentaje) para describir las características demográficas y las puntuaciones medias de los profesionalismos y sus dimensiones. Para evaluar la normalidad se utilizaron los histogramas y las pruebas de sesgo-curtosis y Shapiro-Wilk. Las comparaciones entre los dos grupos se realizaron mediante la prueba t de muestras independientes. Para comparar más grupos se utilizó la prueba de Kruskal-Walli. Resultado: Los hallazgos de este estudio muestran que la puntuación media de profesionalismo fue de 75,26(±10,5), la media más alta se relacionó con la dimensión de comportamiento basado en valores y normas profesionales (80,36 ± 9,93) y la media más baja se relacionó con la dimensión de interacciones profesionales (75,00 ±13,72). Los estudiantes con participación regular perfecta en su pasantía tuvieron un puntaje de profesionalismo significativamente más alto que otros estudiantes (valor p = 0.0001). No hubo relación significativa entre el género de los estudiantes y el puntaje de profesionalismo (p < 0.571). Conclusión: Dada la importancia de la familiarización de los estudiantes de pregrado con los conceptos de profesionalismo en teoría, brindar capacitación práctica de estos conceptos a través de instructores experimentados y modelos a seguir puede ser un paso efectivo para desarrollar el profesionalismo en las enfermeras después de su graduación.